Ecological studies of aquatic moss pillars in Antarctic lakes 2. Temperature and light environment at the moss habitat - Kudoh, Sakae; Watanabe, Kentaro; Imura, Satoshi (National Institute of Polar Research, 2003)
P(論文) To understand the environmental conditions, which control the growth of moss pillars in lake bottoms, water temperature and light in the moss pillar habitat in lake Kuwai Ike in Skarvsnes, Soya Coast, East Antarctica, were continuously measured for about one year, February 1999 to Jannuary 2000. Limnological characteristics of surface water of the lake were investigated in summer 2000, and compared with those in four neighboring lakes. Low contents of ions, neutral pH and dissolved oxygen in saturation level in the surface water in Kuwai-Ike lake were comparable to the values of the other oligotrophic freshwater lakes in Soya Coast and Schirmacher Oasis, located in Queen Maud Land, East Antarctica. The temperature at the lake bottom showed uni-modal seasonal change, in the range 0-12°C. Several sudden temperature drops of > 2°C within a few hours were recorded in the ice-free autumn season; they may have been correlated with the wind-induced vertical mixing events which occurred before complete ice cover development on the lake surface. Light reaching the lake bottom showed clear diel and seasonal fluctuations, and the flux density was strongly affected by the attenuations of water, ice and snow: the photosynthetically active radiation (PAR) measured at the lake bottom was < 50% of that at ground level even in ice-free autumn, and decreased further in ice covered seasons. The instantaneous PAR flux <10μmol m^<-2> s^<-1> was recorded for nearly 2 months in winter; however, daily fluxes over 1 mol m^<-2> day^<-1> were recorded for the other ca. 8 months, with >100μmol m^<-2> s^<-1> of instantaneous peak fluxes around noon. departmental bulletin paper